Modulo Loss Reduction for Vector Perturbation Systems - Han, Hyeon-Seung; Park, Seok-Hwan; Lee, Sunho; Lee, Inkyu (IEEE transactions on communications, 2010)
In this letter, we present an improved precoding technique which reduces a modulo loss in vector perturbation with low complexity. Instead of searching perturbation vectors in the infinite lattice, the proposed scheme restricts the search range by utilizing the distribution of the perturbation vector depending on transmitted data. As a result, we can achieve significant complexity savings at the transmitter while providing better performance compared to the original vector perturbation.